Power Electronics Building Block (PEBB) hardware design and reliability prediction - Toh C.L.; Wong Y.M.; Norum L.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Architectural design; Failure analysis; Hardware; Power converters; Power electronics; Reliability; Reliability analysis; Software design; Stress analysis; Communication interface; Failure rate; Hardware and software designs; Modular multilevel converters; Power Electronics Building Blocks; Power electronics converters; Reliability block diagrams; Reliability prediction; Outages